The use of performance analysis and data driven approaches within senior men's football recruitment - Frost, W.; Groom, R.; Nicholls, S. B. (International Journal of Sports Science & Coaching, 2025)
Football clubs face various demands due to transfer fee increases within player recruitment, leading to numerous clubs adopting alternate methods to remain competitive within the transfer market. This study aimed to investigate the use of video and data based performance analysis (PA) within player recruitment. Participants (n = 19) from professional and semi-professional football clubs were invited to complete a survey through LinkedIn incorporating Likert scale and open text responses. The survey consisted of three sections: demographics, use of PA in recruitment, and perceptions of PA in recruitment. Data was analysed using Mann Whitney U and/or thematic analysis where appropriate to understand the difference in approach between experienced/inexperienced recruiters. Four key themes were identified as formulating the recruitment cycle, these were 1) video and data usage as a crucial tool, 2) identification of hidden talent using external datasets, 3) performance profiling to quantify strengths/weaknesses and provide pertinent insights into a player's abilities, and 4) due diligence to assess a player's personality and cultural fit. The significance of this work has enabled the creation of a novel empirically grounded recruitment analysis framework. In doing so, this study makes an original empirical and conceptual contribution to our understanding of player recruitment in football to inform applied practice.